Response of Pulut Maize (Zea mays Ceratina) to Corn Cob Biochar as Soil Improver - Christa Dyah Utami; Sultan Ghalib Murtadho (KHD Production, 2025)
Pulut corn is one of the corn varieties consumed by Indonesians for its nutritional content. However, its production has declined due to suboptimal land conditions, such as water deficit and low organic matter content. This research was conducted in Kebonsari, Sumbersari Subdistrict, Jember District, from August to October 2024, on land at 100 meters above sea level with a temperature of 26-31°C, humidity of 88-90%, and rainfall of 6-20 mm/day. The study used a non-factorial Randomized Group Design (RAK) with six doses of corn cob biochar (0.8 kg/m2, 1.6 kg/m2, 2.4 kg/m2, 3.2 kg/m2, 4 kg.m2, and 4.8 kg/m2) and four replications. Variables observed included vegetative growth and yield of pulut corn plants, such as plant height, stem diameter, number of leaves, sweetness content, cob length and diameter, and fresh and dry weight. The results showed that the biochar dose of 1.6 kg/m² gave a very significant effect on fresh cob weight per sample (1.08 kg) and dry weight per sample (0.23 kg). Meanwhile, the dose of 0.8 kg/m² had a significant effect on fresh weight (2.60 kg) and dry weight per plot (1.91 kg). Biochar effectively improves soil structure, increases microorganisms, and supports the growth and production of pulut corn.